Concrete overlay versus Reconstructing as a repair method to damaged concrete pavement at the Durban Container Terminal - Naicker, R.; Allopi, D (IJRDO - Journal of Social Science and Humanities Research, 2016)
Concrete overlays for concrete pavement have not been used locally, but there is extensive experience of the method abroad and particularly in the USA, where concrete as a paving material in port terminals, airports and highways remains popular. Asphalt overlays have been used more extensively locally, and recently in the Gauteng Freeway improvement programme, where both unreinforced, jointed and continuously reinforced, un-jointed pavements have been overlaid. For container terminals, asphalt overlays are not an option because of the high loading applied, particularly in the container stacks. The method proposed for the Durban Container Terminal (DCT) is therefore for a reinforced concrete overlay. Alternatives using steel or polypropylene fibres have been investigated but have not been pursued because of cost and other considerations. Given that the bulk of the terminal paving is intact, and severely stressed areas either have been, or are programmed to be repaired, the construction of an overlay is an option as construction time is minimized, resulting in reduced terminal disruption, the remaining capacity of the existing pavement is utilized, construction cost is lower than reconstruction and this option is more environmentally acceptable.